Dosing recommendation of nirmatrelvir/ritonavir using an integrated population pharmacokinetic analysis - Phylinda L. S. Chan; Ravi Shankar P. Singh; Donna S. Cox; Haihong Shi; Bharat Damle; Timothy Nicholas (Wiley, 2023)
Abstract Protease inhibitor nirmatrelvir coadministered with ritonavir as a pharmacokinetic enhancer (PAXLOVID™; Pfizer Inc) became the first orally bioavailable antiviral agent granted Emergency Use Authorization in the United States in patients ≥12 years old with mild to moderate coronavirus disease 2019 (COVID‐19). This population pharmacokinetic analysis used pooled plasma nirmatrelvir concentrations from eight completed phase I and II/III studies to characterize nirmatrelvir pharmacokinetics when coadministered with ritonavir in adults with/without COVID‐19. Influence of covariates (e.g., formulation, dose, COVID‐19) was examined using a stepwise forward selection (α = 0.05) and backward elimination (α = 0.001) approach. Simulations with 5000 subjects for each age and weight group and renal function category were performed to support dosing recommendations of nirmatrelvir/ritonavir for adults with COVID‐19 and guide dose adjustments for specific patient populations (e.g., renal insufficiency, pediatrics). The final model was a two‐compartment model with first‐order absorption, including allometric scaling of body weight and dose‐dependent absorption (power function on relative bioavailability). Nirmatrelvir clearance (CL) increased proportionally to body surface area-normalized creatinine CL (nCLCR) up to 70 ml/min/1.73 m2 and was independent of nCLCR above the breakpoint. Significant covariates included carbamazepine or itraconazole coadministration as markers for drug interactions, COVID‐19 on CL, formulation on relative bioavailability, and age on central volume of distribution. Simulation results support current dosing recommendations of nirmatrelvir/ritonavir 300/100 mg twice daily (b.i.d.) in adults with normal renal function or mild impairment and pediatrics (12 to <18 years) weighing ≥40 kg and nirmatrelvir/ritonavir 150/100 mg b.i.d. in adults with moderate renal impairment.